Extracorporeal membrane oxygenation as a bridge to transplant in neonates with fatal pulmonary conditions: A review. (December 2022) - Johnson, Brandy; Dobkin, Shoshana Leftin; Josephson, Maureen
Abstract: Neonates with progressive respiratory failure should be referred early for subspecialty evaluation and lung transplantation consideration. ECMO should be considered for patients with severe cardiopulmonary dysfunction and a high likelihood of death while on maximal medical therapy, either in the setting of reversible medical conditions or while awaiting lung transplantation. While ECMO offers hope to neonates that experience clinical deterioration while awaiting transplant, the risks and benefits of this intervention should be considered on an individual basis. Owing to the small number of infant lung transplants performed yearly, large studies examining the outcomes of various bridging techniques in this age group do not exist. Multiple single-centre experiences of transplanted neonates have been described and currently serve as guidance for transplant teams. Future investigation of outcomes specific to neonatal transplant recipients bridged with advanced devices is needed.